InterZonale 1945 : Konferenz der Bilder - Bergmann, Hans-Georg; Schmidt, Hans-Werner; von Graevenitz, Antje; Jonas-Edel, Justus; Kunsthalle zu Kiel; Schleswig-Holsteinischer Kunstverein, Kiel (Kiel : Schleswig-Holsteinischer Kunstverein, 1995)
Ackermann, Max ; Balden, theo ; Baumeister, Willi ; Beckmann, Max ; Beuys, Joseph ; Bissier, Julius ; Breuer, Leo ; Brockmann, Gottfried ; Bruse, Hermann ; Cavael, Rolf ; Dienz, Herm ; Dix, Otto ; Ende, Edgar ; Ernst, Max ; Felixmüller, Conrad ; Glöckner, Hermann ; Götz, Karl Otto ; Goller, Bruno ; Grundig, Hans ; Grundig, Lea ; Heartfield, John ; etc.
InterZonale 1945 : Konferenz der Bilder, Schleswig-Holsteinischer Kunstverein, Kunsthalle zu Kiel, 7. Mai - 2. Juli 1995
boek